LASER-INDUCED RESONANCES IN HIGH N STATES OF HYDROGEN-LIKE F-19(8+) - Silver, J; Jelley, N; Mcintyre, L (1977)
A laser resonance technique using Doppler tuning has been applied to measure transitions between highly excited states of highly ionized fluorine. Resonance transitions between n=9 and n=10 levels of 19F8+ with a mean wavelength of 4796.06±0.24 Å were observed. This wavelength is close to the calculated value of 4796.16 Å for the wavelength of the 92L17/2-102M19/2 transition.